천연 무기응집제를 이용한 조류 제거 - 김석구(Seog Ku Kim); 김동관(Dong Kwan Kim); 강성원(Sung Won Kang); 안재환(Jaehwan Ahn); 김일호(Il Ho Kim); 윤상린(Sang Leen Yun); 이상협(Sang Hyup Lee); 이원태(Won Tae Lee) (Daehan hwan'gyeong gonghag hoeji, 2013)
Coagulation and sedimentation tests were conducted with clay and three different coagulants of soil origin (AC-A, AC-B, AC-C) to determine optimal coagulant types and doses to remove algae in stagnant water bodies such as reservoirs. Raw water had an algal density of 2,950 cells/mL and was dominated by Cyanobacteria. Removal rates of algal density by clay (50 mg/L) were 49% and 85% after 10 and 30 minutes sedimentation, respectively. Other natural coagulants achieved 80-90% removal in 10 minutes and 89-94% removal in 30 minutes of sedimentation after adding 20 mg/L each. AC-A was the optimal coagulant from this study considering algal removal rates and other water quality parameters such as turbidity and pH. For the same removal rates of algae, raw waters with higher algal densities required higher coagulant doses although no strong corelation was observed. The coagulants of soil origin did not impact orgnic contents and pH of raw water, but remove phosphate up to 70%. 조류 발생이 문제시 되는 정체수역이나 호소에서 현장적용에 적합한 응집제를 선정하고 응집제별 적정 주입농도를 찾기 위하여 황토와 개량된 토양기반 무기응집제 세 가지(AC-A, AC-B, AC-C)를 주입하며 응집 침전실험을 실시하였다. 남조류가 주종이고 조류밀도가 2,950 cells/mL인 원수에 대한 황토(50 mg/L 주입)에 의한 조류밀도 제거율은 10분 침전후 49%, 30분 침전후 85%로 나타났고, 다른 세 가지 무기응집제(20 mg/L 주입)의 경우 10분 침전 후 80-90% 제거율, 30분 침전 후에는 89-94%의 조류 제거율을 나타냈다. 조류 제거와 탁도, pH 등의 수질인자 특성을 종합적으로 고려할 때 본 연구에서 고려된 천연 무기응집제 중 AC-A가 가장 적합한 것으로 판단된다. 원수의 조류밀도가 높을수록 같은 제거효율을 얻기 위한 응집제 주입량이 증가하는 경향을 나타냈으나 선형적인 상관관계는 찾을 수 없었다. 황토를 비롯한 천연 무기응집제는 원수의 유기물 제거 및 pH 변화에는 큰 영향을 미치지 않는 것으로 나타났고, 인산염의 경우 주입량을 늘임에 따라 제거율이 높아져 최대 70%까지 제거되었다.